Argos mutants define an affinity threshold for spitz inhibition in vivo. - Alvarado, D.; Evans, T.A.; Sharma, R.; Lemmon, M.A.; Duffy, J.B. (Journal of Biological Chemistry, 2006)
Argos, a secreted antagonist of Drosophila epidermal growth factor receptor (dEGFR) signaling, acts by sequestering the activating ligand Spitz. To understand how different domains in Argos contribute to efficient Spitz sequestration, we performed a genetic screen aimed at uncovering modifiers of an Argos misexpression phenotype in the developing eye. We identified a series of suppressors mapping to the Argos transgene that affect its activity in multiple developmental contexts. These point mutations map to both the N- and C-terminal cysteine-rich regions, implicating both domains in Argos function. We show by surface plasmon resonance that these Argos mutants are deficient in their ability to bind Spitz in vitro. Our data indicate that a mere approximately 2-fold decrease in K(D) is sufficient to compromise Argos activity in vivo. This effect could be recapitulated in a cell-based assay, where a higher molar concentration of mutant Argos was needed to inhibit Spitz-dependent dEGFR phosphorylation. In contrast, a approximately 37-fold decrease in the binding constant nearly abolishes Argos activity in vivo and in cellular assays. In agreement with previously reported computational studies, our results define an affinity threshold for optimal Argos inhibition of dEGFR signaling during development.